Evaluation of effective factors in maskability of tinnitus - Maryam Emadi; Atta Heidari; Vahid Rashedi; Farhad Farahani (Vesnu Publications, 2013)
Introduction: Tinnitus is one of the most common symptoms of patients referred to audiology clinics affecting more than 10% of the adult population. An important feature of tinnitus is its maskability which has been considered as a physiologic treatment. In this study, the role of various factors on tinnitus masking such as the loudness and frequency of tinnitus, hearing loss and the location of tinnitus has been studied. Materials and Methods: In this descriptive-analytic study, 45 patients with tinnitus, who were referred to the audiology clinic of Hamadan rehabilitation faculty, were evaluated via various audiometric tests including determination of tinnitus loudness and tinnitus frequency, minimum masking levels and residual inhibition. Maskability has been determined on the basis of residual inhibition test that used narrow band noise at 10 dB above minimum masking level for 1minute. All tests were performed with Madsen OB822 audiometer. Results: The results showed that 46.7% of subjects who evaluated for tinnitus had complete maskability and 35.6% of them had partial maskability. Only 17.6% of these patients could not be masked. The results showed that there is a relationship between tinnitus loudness and maskability. Moreover, no relation between maskability, tinnitus frequency and hearing loss were found. Results did not show any relationship between location of tinnitus and maskability. Conclusion: The result of this research shows that tinnitus will be masked in considerable percentage of individuals and this method can be used to control and relieve related symptoms. Keyword: Tinnitus, Maskability, Sound therapy.